1991
DOI: 10.1002/pros.2990180204
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the prostate of the neonatally estrogenized mouse

Abstract: Neonatal estrogenization of the mouse with diethylstilbestrol resulted in time-of-exposure and dose-dependent inhibition of the growth of the prostatic lobes observed at the age of 2 mon. The critical time was the days 1-6 of postnatal life. In neonatally estrogenized (neoDES) mice, responses to 5 alpha-dihydrotestosterone in terms of nuclear 3H-thymidine labelling were altered concomitantly with the inhibition of growth and were in accordance with changes in the relative volumes of epithelium, glandular lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 20 publications
8
41
0
1
Order By: Relevance
“…Estrogens elicited a marked stimulation of fibromuscular stroma both in proportional and absolute terms, confirming it as being the primary site for estrogen action and implicate complex mesenchymalepithelial interactions to induce changes at the epithelial level. Similar effects were reported by Pylkkanen et al (1991) who showed localized hyperplasia and dysplasia at distinct sites of the mouse urethro-prostatic complex and increased the expression of the proto-oncogene, c-myc in the prostate after neonatal estrogenization. This increase is believed to be associated with increased prostatic dysplasia in mice (Pylkkanen et al 1993) which is the most common possible pre-malignant lesion of the prostate and may represent the initial transformation event in the majority of prostate cancers (McNeal & Bostwick 1986, McNeal 1991.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Estrogens elicited a marked stimulation of fibromuscular stroma both in proportional and absolute terms, confirming it as being the primary site for estrogen action and implicate complex mesenchymalepithelial interactions to induce changes at the epithelial level. Similar effects were reported by Pylkkanen et al (1991) who showed localized hyperplasia and dysplasia at distinct sites of the mouse urethro-prostatic complex and increased the expression of the proto-oncogene, c-myc in the prostate after neonatal estrogenization. This increase is believed to be associated with increased prostatic dysplasia in mice (Pylkkanen et al 1993) which is the most common possible pre-malignant lesion of the prostate and may represent the initial transformation event in the majority of prostate cancers (McNeal & Bostwick 1986, McNeal 1991.…”
Section: Discussionsupporting
confidence: 84%
“…Although ductal tips with DES were significantly reduced compared with EB treatment, VP weight was unaffected owing partially due to increased epithelial width or fibromuscular stroma with DES treatment. Similar reductions in prostate size and alterations in the prostatic composition have also been reported by perinatal exposure to DES or estradiol in rodents in earlier studies (Chung & MacFadden 1980, Higgins et al 1981, Naslund & Coffey 1986, Pylkkanen et al 1991. These long-term alterations might be due to differentiation defects induced in prostatic cells as a result of neonatal estrogen exposure that results in their abnormal pattern of growth later in life (Weinberg 1991).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Previous studies by us and others have shown prostatic epithelial dysplasia and inflammatory cell infiltration in the prostates of mice as they age, after they were transiently treated with estrogen during neonatal life. 10,22,34,35 This estrogen-induced inflammatory response also appears to be specifically mediated by ER␣: ER␣ knockout mice show no prostatic response to neonatal diethylstilbestrol, but ER␤ knockout mice show a response similar to that observed in wild-type animals. 12 The observation that estrogen is linked to the development of prostatic inflammation is particularly significant as estrogens, in addition to androgens, have also been implicated in the development of PCa.…”
Section: Estrogens Prostatitismentioning
confidence: 91%
“…There is strong experimental evidence that, at least in rodents, excessive or untimely exposure to estrogens can induce prostatic neoplasia. [1][2][3][4][5][6] Moreover, aromatizable but not nonaromatizable androgens can cause prostate cancer. 7,8 On the other hand, impaired estrogen action can also lead to structural and functional abnormalities in prostatic epithelium, as has been demonstrated in estrogen receptor (ER)-␤ 9 or aromatase-deficient mice.…”
mentioning
confidence: 99%